Implementasi Pembiasaan Akhlak Dalam Meningkatkan Pendidikan Karakter Religius Siswa - Zahro, Fatimatuz; Pahrurroji, Pahrurroji (Prodi Pendidikan Keagamaan Islam, 2024)
The purpose of this research is to find out how the implementation of learning aqidah akhlak in SDIT Al-Ummah improves religious character education in students, as well as know what are the supporting and inhibiting factors. The research methods used are qualitative with a descriptive approach. Data analysis techniques consist of data reduction, data presentation, and conclusion drawing of verification. The results of the research obtained are: The implementation of moral aqidah learning carried out in improving religious character education is by the existence of moral habits which are divided into 4 activities, namely routine activities, spontaneous activities, exemplary activities and programmed activities. As for habits that are carried out, such as the 5S culture (Smile, greet, be polite, polite), praying before and after studying, cooperating, helping, giving advice by teachers, discipline regarding health, midday prayer in congregation, study, memorization and repeating memorization and so on.. The supporting factors are the motivation and role of teachers, adequate facilities, and family environment. As for inhibiting factors, namely the lack of motivation in students, lack of family support, and the association of students.